PENGUKURAN KUALITAS WEBSITE E-LEARNING UNIVERSITAS ISLAM NEGERI SUMATERA UTARA MENGGUNAKAN METODE WEBQUAL 4.0 - Ulfa Fadilah; Triase Triase; Raissa Amanda Putri (Smart Education, 2024)
Abstract: This research uses the webqual 4.0 model which corrects the three variables usability, information quality, service interaction quality and an additional variable, namely overall impression. This research aims to improve the quality of website services and e-learning website services at the State Islamic University of North Sumatra. The research sample consisted of 365 people, where the sample was taken using simple random sampling with a youth table. Data was collected through a questionnaire containing statements about user perceptions of the website. This data will be used to obtain the Webqual Index value which is used to determine the service quality value. The results of the webqual index value for each variable are usability of 0.85, information quality of 0.86, service interaction quality of 0.86 and overall impression of 0.85. The variables that most influence the service quality of the North Sumatra State Islamic University e-learning website in general for respondents are the information quality and service interaction quality variables with a webqual index of 0.86. The results of the webqual index measurement show that the quality of the e-learning website of the North Sumatra State Islamic University is very good with a webqual index value of 0.86.. Keywords: Website, Webqual, Information Quality, Usability Dan Service Interaction Quality, Overall Impression Abstrak: Model webqual 4.0 yang digunakan dalam penelitian ini mengoreksi tiga variabel yaitu usability, information quality, service interaction quality dan variabel tambahan yaitu overall impression. Tujuan dari penelitian ini adalah untuk meningkatkan standar layanan website e-learning UINSU. Sampel penelitian berjumlah 365 orang, dimana pengambilan sampelnya menggunakan simple random sampling dengan tabel yount. Data dikumpulkan dengan mensurvei pendapat pengguna tentang situs website. Nilai webqual index yang digunakan untuk menghitung nilai kualitas layanan yang diperoleh dari data. Hasil nilai webqual index masing-masing indikator adalah usability sebesar 0,85, information quality sebesar 0,86, service interaction quality sebesar 0,86 dan overall impression sebesar 0,85. Hasil pengukuran webqual 4.0 menunjukkan bahwa kualitas penyelenggaraan website e-learning UINSU berada pada nilai 0,86 yang berarti sangat baik dalam nilai webqual index. Kata kunci: Website, Webqual, Usability, Information Quality, Service Interaction Quality, Overall Impression